DEVELOPMENT AND OPTIMIZATION OF RAFT-FORMING FORMULATION OF H2BLOCKERS - BHOSALE, MANSI MANOJ; PRAMODKUMAR J SHIROTE (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The present research work is focused to develop in situ raft gel of Nizatidine. sodium alginate (SA) is one of the critical components for the development in situ raft system. Methods: The formulation was prepared using polymers such as SA and gellan gum. The formulations were subjected to evaluation characteristics such as pH, in vitro gelling capacity, viscosity, gel strength, and in vitro release studies. Results: The pH of all the prepared batches was found in the range of 6.4–7.2 for S1–S9, and 6.3–7.2 for G1–G9. S1–S9 formulations showed viscosity in the range of 253.7–400.9 cps, and G1–G9 formulations showed viscosity in the range of 253.4–399.8 cps. Formulation S6 containing SA and G6 containing gellan gum gave the highest drug content of 99.58% and 99.5%, respectively. The highest gel strength 4.6 is exhibited by S6 and G6 formulations. Formulation S6 containing SA gave the highest drug release of 95.62% and also showed sustained and controlled release for up to 12 h. Conclusion: Gastric raft formulation is a better choice for drugs such as Nizatidine which enhances the drug release for a prolonged time by remaining buoyant in the stomach for more than 12 h.